2009
DOI: 10.1111/j.1365-4632.2009.04070.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch test reaction on Ethiopian subjects with eczema

Abstract: A high incidence of positive patch test reactions was identified in the study population, and the introduction of patch testing in Ethiopia is essential for the management of allergic contact dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Our study found nickel as the most frequent contact sensi zer in 22.7% pa ents which was comparable to other studies. [12][13][14][15] Nickel posi vity has shown a female preponderance in our study as reported by Bilcha et al 15 and Bilcha et al 16 . The higher rates of posi ve patch test reac ons for nickel sulfate in females could relate to their ear piercing, cosme c applica on and ornament use behavior.…”
Section: Discussionsupporting
confidence: 85%
“…Our study found nickel as the most frequent contact sensi zer in 22.7% pa ents which was comparable to other studies. [12][13][14][15] Nickel posi vity has shown a female preponderance in our study as reported by Bilcha et al 15 and Bilcha et al 16 . The higher rates of posi ve patch test reac ons for nickel sulfate in females could relate to their ear piercing, cosme c applica on and ornament use behavior.…”
Section: Discussionsupporting
confidence: 85%
“…However, most (83%) of the people from this region live in rural areas where the sanitary conditions are worse. Based on socioeconomic data provided in the Statistical Report of the 2007 Population and Housing Census Results of Federal Democratic Republic of Ethiopia, and on previous studies, we defined the panel of allergens considered in the present study. As also found in a previous report, 50% of our patients showed a positive patch test, and we found basically no difference between women (about 49%) and men (about 51%).…”
Section: Discussionmentioning
confidence: 99%
“…The literacy rate in this region is 51.75%, which is higher than the 15.71% national rate. 6,14,15 we defined the panel of allergens considered in the present study. As also found in a previous report, 16 50% of our patients showed a positive patch test, and we found basically no difference between women (about 49%) and men (about 51%).…”
Section: Discussionmentioning
confidence: 99%
“…Níquel es por excelencia el alérgeno de contacto más frecuente y prevalente en todos los estudios a nivel mundial 17,18,22,23,24,25,26 como también lo es en nuestro estudio. Tiene una frecuencia de 34,28% en mujeres, siendo la más alta del género.…”
Section: Mezcla De Fragancias 14unclassified